The impact of severe drought on survival, fecundity, and population persistence in an endangered amphibian. Issue 2 (26th February 2016) - Cayuela, H.; Arsovski, D.; Bonnaire, E.; Duguet, R.; Joly, P.; Besnard, A.
Abstract: Climate is globally changing. In Europe, studies have highlighted an increasing trend in both the frequency and magnitude of droughts. Abrupt changes in the frequency, location, or intensity of extreme heatwaves and droughts can have direct and severe effects on wild populations. Amphibians are the planet's most threatened group of vertebrates, with over 40% of known species considered in decline. To date, researchers have mainly focused on the influence of repeated droughts on species occurrence and community composition; however, evidence of the direct impact of climatic factors on the demographic parameters of amphibians is currently not well documented. Further investigation of this issue is therefore of critical importance in order to optimize local and global wildlife conservation policies in the context of a changing climate. This study used capture–recapture data to investigate the impact of severe drought on the survival and fecundity of a threatened amphibian, the yellow‐bellied toad ( Bombina variegata, L.), as well as to predict how potential changes in the frequency of droughts might influence the population growth rate. By developing multievent capture‐recapture models, we showed that severe drought has a negative impact on fecundity and postmetamorphic survival at different ontogenetic stages. Then, using stochastic matrix population models, we predicted that changes in drought frequency negatively influence the population growth rate, which is a warning sign for population persistence. Direct conservation actions are then proposed to mitigate the detrimental effects of drought on population dynamics.